Estimation of Arterial Nonlinear Compliance using Ultrasound Images - Kopustinskas, A.; Kupciunas, I.; Marcinkeviciene, J. (Elektronika ir Elektrotechnika, 2010)
In order to better detect the early stage of disease nonlinear compliance of artery is considered. Algorithm and MATLAB program analysis M and D mode ultrasound images is created. Program applied for the calculation internal radius of artery and blood flow during the cardiac cycle. Nonlinear Windkessel artery model and by sphygmomanometer calibrated typical blood pressure waveform used for calculation parameters a and b, characterizing exponential dependence compliance with pressure. Experiment “in vivo” with local caro-tid artery show, that a vary in the range (2,52…3,29) ml/mmHg, b – (0,014…0,021) mmHg-1, volume compliance – (0,2…1,2) ml/mmHg. These values match with data, presented in the literature. Direct real time ultrasound measurements of local arterial radius, intima-media thickness and blood velocity allow to increase the plausibility of estimation.